2021
DOI: 10.21608/asalexu.2021.219100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Educational Intervention on Self-Care Practices among Patients with Diabetic Retinopathy

Abstract: Background: Diabetic retinopathy (DR) is the most common ophthalmic complications of diabetes mellitus (DM) and is one of the leading causes of vision impairment and vision loss. Timely intervention, and self-care practices measures can delay or prevent subsequent loss of vision.Objective: This study aimed to evaluate the effect of an educational intervention on self-care practices among patients with diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Karakurt and Kaşıkçı (23,25). In a study on DR individuals, it was stated that 62.7% of the patients with DR had an acceptable level of general self-care activities (21). In the present study, it was found that income level did not affect DR self-care mean scores.…”
Section: Evaluation Of Datasupporting
confidence: 42%
See 2 more Smart Citations
“…Karakurt and Kaşıkçı (23,25). In a study on DR individuals, it was stated that 62.7% of the patients with DR had an acceptable level of general self-care activities (21). In the present study, it was found that income level did not affect DR self-care mean scores.…”
Section: Evaluation Of Datasupporting
confidence: 42%
“…Since it is thought that it may affect the results of the study, patients who were within the following inclusion criteria were included in the study, in line with the literature (6,(17)(18)(19)(20)(21). Patients who volunteered to participate in the study, had been diagnosed with DR at least 6 months ago, were 18 years of age or older, had the cognitive ability to answer the survey questions, and did not have any psychiatric diagnosis were included in the sample group.…”
Section: Participantmentioning
confidence: 99%
See 1 more Smart Citation
“…Making patients knowledgeable about the disease, engaging them in self-care practices, and helping them in adopting a new life style are very essential to achieve treatment goals, to keep the disease under control, and to prevent complications (Shaban, 2018). Therefore, this study was carried out to test the hypothesis that implementing the educational program for DR patients would improve their knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Visual impairment secondary to diabetic retinopathy represents a major public health problem which affects negatively on patients' life. Improving patient's knowledge and awareness about the disease, engaging them in self-care practices, and helping them in adopting a healthy life style are very essential to prevent progress of the disease and to prevent visual impairment (Shaban, 2018;Abid, 2022). The majority of patients with diabetes can significantly reduce the chances of developing long-term complications as DR by improving their knowledge.…”
Section: Introductionmentioning
confidence: 99%